Implementación de un modelo multietapa de planificación conjunta de la expansión de la generación y transmisión para el sistema nacional Interconectado de Ecuador. - Aguaiza Quinapanta, Cristhian Paul (2023)
In the current context of growing energy demand and the need for efficient and sustainable planning of electricity systems, the implementation of a multi-stage model for joint planning of generation and transmission expansion is presented as a strategic alternative to traditional separate planning, which has generated additional costs and limitations in the face of growing energy demand. In this research work, a multi-stage model of joint planning of generation and transmission expansion for the National Interconnected System of Ecuador (SNI) is implemented in order to evaluate solutions that minimize the costs of operation and construction of new infrastructure. A mixed integer linear programming MILP model is applied to analyze the expansion of electricity generation and transmission in Ecuador for the period 2018-2031. For this purpose, a reduced equivalent system of the SNI of Ecuador, developed by the authors and named 56-Bus SNI Ecuador System, at 230 kV and 500 kV levels, is used as a starting point. The results obtained show that joint planning can significantly reduce investment and operation costs in the long term with respect to separate planning. Finally, this work represents an important contribution to the optimization of generation and transmission expansion planning in Ecuador, offering a more integrated and cost-effective vision for the future of the electrical infrastructure.